Castoffs of capital : work and love among garment workers in Bangladesh - Karim, Lamia (University of Minnesota Press, 2022)
"Dispelling stereotypes about garment workers in the global apparel industry Castoffs of Capital examines how female garment workers experience their work and personal lives within the stranglehold of global capital. Drawing on fieldwork in Bangladesh, anthropologist Lamia Karim focuses attention onto the lives of older women aged out of factory work, heretofore largely ignored, thereby introducing a new dimension to the understanding of a female-headed workforce that today numbers around four million in Bangladesh. Bringing a feminist labor studies lens, Castoffs of Capital foregrounds these women not only as workers but as mothers, wives, sisters, lovers, friends, and political agents. Focusing on relations among work, gender, and global capital's targeting of poor women to advance its market penetration, Karim shows how women navigate these spaces by adopting new subject formations. She locates these women's aspirations for the 'good life' not only in material comforts but also in their longings for love and sexual fulfillment that help them momentarily forget the precarity of their existence under the shadow of capital. Through richly detailed ethnographic studies, this innovative and beautifully written book examines the making and unmaking of these women's wants and desires, loves and tribulations, hopes and despairs, and triumphs and struggles."--